2014
DOI: 10.14260/jemds/2014/2591
|View full text |Cite
|
Sign up to set email alerts
|

A New and Safer Surgical Technique Figure of Eight Sti T Ch for Management of Perforated Peptic Ulcer

Abstract: There are many methods for closing the perforated peptic ulcer. The technique of closure of perforation by figure of 8 stitch method has been found to be very effective in managing patients with this common problem. MATERIAL AND METHOD: The present study was conducted in Unit III of Department of General Surgery, Government Medical College and Dr. Susheela Tiwari Government Hospital Haldwani, from January 2012 to December 2013 on the cases of peptic ulcer perforation peritonitis. All patients with clinical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…6 Choudhary et al, in their study assessing figure of 8 technique reported that the average time of presentation was between 3-4 days, earliest up to 2-3 hours and delayed up to 7-8 days. 12 Delay in PUD perforation before surgical treatment is a strong determinant for increased complication rates and hospital costs. 13…”
Section: Day Of Presentationmentioning
confidence: 99%
“…6 Choudhary et al, in their study assessing figure of 8 technique reported that the average time of presentation was between 3-4 days, earliest up to 2-3 hours and delayed up to 7-8 days. 12 Delay in PUD perforation before surgical treatment is a strong determinant for increased complication rates and hospital costs. 13…”
Section: Day Of Presentationmentioning
confidence: 99%